2007
DOI: 10.1021/ic061901x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phase Transition Pathways in X3H(SO4)2 (X = Rb, NH4, K, Na):  Variable Temperature Single-Crystal X-ray Diffraction Studies

Abstract: Evaluation of phase transitions in a series of hydrogen sulfates (Rb3H(SO4)2, (NH4)3H(SO4)2, K3 H(SO4)2, and Na3H(SO4)2) based on the single-crystal structure analysis has revealed the exact nature of such transitions and has sorted out the various ambiguities involved in earlier literature. Rb3H(SO4)2 at 293 K is C2/c. It is isostructural to its ammonium analogue, (NH4)3H(SO4)2, at room temperature. However, the variable temperature single-crystal diffraction studies indicate that the phase transition mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…(4) and (5) and the direct dehydration of Rb 3 H(SO 4 ) 2 to Rb 2 SO 4 and Rb 2 S 2 O 7 , which is expected to occur under very dry conditions prior to the disproportionation reaction. Finally, it should be noted that possible polymorphic transitions of Rb 3 H(SO 4 ) 2 between various monoclinic forms at intermediate temperatures, as suggested by Swain and Row [21] would not change the general features of the phase diagrams shown in Fig. 6.…”
Section: Discussion: Proposed Phase Diagrams In the Rb 2 So 4 -H 2 Somentioning
confidence: 81%
See 1 more Smart Citation
“…(4) and (5) and the direct dehydration of Rb 3 H(SO 4 ) 2 to Rb 2 SO 4 and Rb 2 S 2 O 7 , which is expected to occur under very dry conditions prior to the disproportionation reaction. Finally, it should be noted that possible polymorphic transitions of Rb 3 H(SO 4 ) 2 between various monoclinic forms at intermediate temperatures, as suggested by Swain and Row [21] would not change the general features of the phase diagrams shown in Fig. 6.…”
Section: Discussion: Proposed Phase Diagrams In the Rb 2 So 4 -H 2 Somentioning
confidence: 81%
“…Finally, as part of a proton NMR study, Suzuki and Hayashi [20] observed an endothermic transition in Rb 3 H(SO 4 ) 2 at 207°C, which they also assigned to a superprotonic transition. In general, the transitions reported by Ichikawa at 56 and 126°C have not been reproduced, although single crystal X-ray diffraction studies by Swain and Row [21] suggest possible transformations between different monoclinic forms at these temperatures.…”
Section: Introductionmentioning
confidence: 87%
“…The majority of papers in the literature supports the choice of centrosymmetric space group C12=c1 (No. 15) in the conventional setting of the International Tables for Crystallography (Hahn, 2002) with lattice parameters a C = 15.431 (8), b C = 5.861 3, c C = 10.169 (5) Å and C = 101.83 (5) (Swain & Row, 2007;Dominiak et al, 2003;Friese et al, 2002). In older publications a different choice of basis vectors (viz.…”
Section: Single-crystal Neutron Diffractionmentioning
confidence: 99%
“…Phase I is paraelastic and phase II is ferroelastic. Crystal structure analysis of TAHS in phases I, II, III, IV and V have only been performed so far by single-crystal X-ray diffraction (Swain & Row, 2007;Dominiak et al, 2003;Friese et al, 2002). However, the proton disorder in the hydrogen bond of the (SO 4 )H(SO 4 ) dimer and of the NH 4 groups cannot be described sufficiently with X-ray diffraction methods.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, the causes of changes in physical properties of K 3 H(SO 4 ) 2 crystals remained unclear. In 1990, their room temperature atomic structure was determined [26]; after this time, possible structural mechanisms of their superprotonic conductivity were discussed, including the absence of the phase with trigonal sym metry (see, e.g., [27,28]). Taking into account the room temperature isostructurality of these crystals and Rb 3 H(SeO 4 ) 2 , the possibility of the phase transi tion from the monoclinic to superprotonic trigonal phase C2/c R m would be assumed.…”
Section: Relationship Between the Structure And Properties In M 3 H(xmentioning
confidence: 99%